Time and being in being and time - Dowding, AJ (2019)
This thesis is about the relationship between time and being, and in particular, Martin Heidegger’s account of that relationship in Being and Time. It elaborates two central claims, in both exegetical and substantive terms, each of which challenges a dominant view of Heidegger’s work. First, most readers of Being and Time have focused upon what it says about being, and taken its claims about time as secondary. I challenge this view, arguing that for Heidegger, time is interrelated to being such that one cannot clarify the sense of the latter without first clarifying the sense of the former. I advance a novel conception of time, which I take to be the one Heidegger was working towards. Second, a prevailing interpretation of Being and Time holds that the issue at stake in Heidegger’s project is intelligibility. To be, the view goes, is to be intelligible or meaningful. Against this, I argue that the non-intelligible plays a privileged role in Heidegger’s account of what one is asking after, in asking after being. The thesis proceeds in four chapters. In chapter 1, I investigate the connection between time and the traditional conception of being, developing in the process an account of Heidegger’s term “presence-at-hand” which shows how concerns about time frame Heidegger’s approach to the question of the meaning of being. In chapter 2, I challenge the completeness of the dominant view that for Heidegger being is the intelligibility of what is, arguing that Dasein’s fundamental disclosure of being does not procure entities at all, but a “non-intelligible” sheer presence. In chapter 3, I develop the problem with the traditional conception of time in the context of its incompatibility with Dasein’s disclosure (using Husserl’s phenomenology of time-consciousness to illustrate that the difficulty lies in successfully articulating time’s dynamism, or “flow”), as well as discussing how the dominant reading of Heidegger’s “primordial temporality” falls short in this regard. Finally, in chapter 4, I provide an interpretation of Heidegger’s primordial temporality which resolves that problem, showing how Dasein’s “ecstatic” structure is able to articulate time’s dynamism, and how as such primordial temporality grounds those other temporal characters constitutive of practical and reflective comportment.